(Des)governo Bolsonaro e a publicidade institucional de prevenção à Aids no Brasil de 2019 a 2022: uma análise crítica do discurso - Alves, Mario Bernardo de Oliveira (2024)
The year 2024 marks 43 years of the AIDS epidemic and, despite advances in the areas of Biology and Medicine, we are experiencing what researchers call the third wave of the epidemic. The epidemic of prejudice and stigma. Largely due to the negative effects of the syndrome, but also due to the impact caused by the mediatization of AIDS-related topics. To analyze the advertising discourse about AIDS, based on the campaigns run by the Ministry of Health between the years 2019 and 2022, and how these campaigns have contributed to combating the prejudice and stigma that HIV causes. The research ultimately seeks to appropriate the theme within the scope of institutional communication, especially advertising by the Brazilian Federal Government. The path outlined to elucidate the social problems of AIDS dialogues about power, stigma, prejudice, and exclusion. The data was collected from the collection of advertising campaigns available on the Ministry of Health website aimed at combating chronic diseases and sexually transmitted infections. The collected material was analyzed in the light of Critical Discourse Analysis (CDA), especially using the three-dimensional framework of discourse proposed by Fairclough (2001). The main results indicate that Jair Bolsonaro's administration prioritized simple, little updated content and, in doing so, reinforced the mistaken idea that AIDS is a disease resulting, almost exclusively, from sexual relations in general; and in particular, same-sex relationships. By opting for this line of action concerning institutional communication on HIV/AIDS prevention, not only did it neglect to effectively combat prejudice and stigmatization, but, in a certain way, it reinforced both behaviors.